HUBUNGAN KECEMASAN TERHADAP SMARTPHONE ADDICTION PADA MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS PEMBANGUNAN NASIONAL VETERAN JAKARTA TAHUN 2020 - Devi Afiani (2021)
Smartphone addiction is a condition where individuals feel preoccupied with using a smartphone so that they ignore other areas of life. One of the triggers for smartphone addiction is anxiety. Anxiety is described as an unpleasant mood with a subjective sense of uncertainty and future threats. Owning a smartphone doesn't automatically lead to smartphone addiction. There are various psychological factors such as loneliness, shame, insecurity and impulsivity. Another psychological factor that is thought to cause smartphone addiction is anxiety. This study aims to determine the relationship between anxiety and smartphone addiction in students of the Faculty of Medicine, Universitas Pembangunan Nasional Veteran Jakarta in 2020 by using the Hamilton Anxiety Rating Scale (HARS) and Smartphone Addiction Scale (SAS) questionnaires. This study used a cross sectional design and data analysis with the Somers'd correlation test. The sample size of 96 people was taken using consecutive sampling technique. The results showed that there was a significant relationship between anxiety and smartphone addiction with a strong correlation strength (p = 0.000; r = 0.621).